Enzymatic in situ saccharification of lignocellulosic biomass in ionic liquids using an ionic liquid-tolerant cellulases. (October 2016) - Xu, Jiaxing; Wang, Xinfeng; Liu, Xiaoyan; Xia, Jun; Zhang, Tong; Xiong, Peng
Abstract: Ionic liquids (ILs) have been considered as a class of promising solvents that can dissolve lignocellulosic biomass and then provide enzymatic hydrolyzable holocellulose. However, most of available cellulases are completely or partially inactivated in even low concentrations of ILs. To more fully exploit the benefits of ILs to lignocellulose biorefinery, it is critical to improve the compatibility between cellulase and ILs. In this study, an IL-tolerant cellulase cocktail derived from Penicillium oxalicum GS was isolated from chemicals polluted microhabitats. High hydrolytic activity of the cellulase cocktail was detected in various ILs. In particular, the cellulase cocktail retained 91% initial activity in IL dimethylimidazolium methylphosphonate ([Dmim][(OCH3 )2 PO2 ]) (20%, w/v), which was effective in disrupting compact structures of rice straw. Furthermore, the cellulase cocktail even preserved 61% initial activity in 25% (w/v) [Dmim][(OCH3 )2 PO2 ] media. A compatible cellulase-IL system, which combines IL pretreatment and subsequent enzymatic saccharification of lignocellulosic biomass into a single vessel, was then developed based on the cellulase cocktail and [Dmim][(OCH3 )2 PO2 ]. Its use significantly improved the saccharification rate of rice straw from 47% to 83% versus the control. Graphical abstract: Highlights: A novel IL-tolerant cellulase cocktail derived from chemicals polluted microhabitats. Utilization of [Dmim][(OCH3 )2 PO2 ] for pretreatment of lignocellulosic biomass. High activity of the cellulase in presence of various ILs. An efficient IL-cellulase media for in situ enzymatic saccharification of biomass.